Five new species of grass cicadas in the genus Graminitigrina (Hemiptera: Cicadidae: Cicadettinae: Cicadettini) from Queensland and Northern Territory, Australia: comparative morphology, songs, behaviour and distributions - Ewart, A.; Popple, L.w.; Hill, K.b.r (Zootaxa, 2017)
Five new species of small grass cicadas belonging to the genus Graminitigrina Ewart and Marques are described, together with detailed analyses of their calling songs. Four species occur in Queensland, G. aurora n. sp. from eastern central Queensland near Fairbairn Dam; G. flindensis n. sp. from central Queensland between Hughenden northwards for at least 108 km; G. einasleighi n. sp. from near The Lynd, Einasleigh River, northeastern Queensland; G. selwynensis n. sp. from the Selwyn Range, northwestern Queensland, at locations about 40 km east of Mount Isa and 25 km southwest of Cloncurry, this latter here transferred from G. bowensis Ewart and Marques; G. uluruensis n. sp. from Uluru and the Olgas in southwestern Northern Territory, extending northwards through Tennant Creek and apparently further north to near Larrimah, a linear distance of approximately 1190 km. These new species bring the known Graminitigrina species to ten, all superficially similar in colour and morphology. A key to male specimens is provided for the 10 species. Additional distribution records and additional aural song recordings are presented for G. bowensis, these requiring the transfer of populations previously identified as G. bowensis from Croydon and Georgetown, northern Gulf region, to G. karumbae Ewart and Marques. Detailed comparative analyses, including NMDS analyses, of the songs of all 10 species are provided, which show that the song parameters are appropriate to distinguish the species, although some partial overlap is noted in the waveform plots between the songs of G. uluruensis n. sp. and G. flindensis n. sp. Regional variations of song parameters are noted in the calling songs of most of the species described.